Aspectual reduplication in Sign Language of the Netherlands: reconsidering phonological constraints and aspectual distinctions - van Boven Cindy (Linguistics)
This study investigates the use of predicate reduplication to express aspectual meaning in Sign Language of the Netherlands (NGT). The study focuses on three aspect types that have been found to be encoded by reduplication across sign languages – habitual, continuative, and iterative – and addresses potential phonological restrictions. Naturalistic corpus data and data elicited from six deaf NGT signers were taken into account. The results suggest that (i) predicate reduplication can express all three aspect types, but it is optional; (ii) reduplication expressing habitual and continuative aspect appears to be phonologically constrained; and (iii) such phonological constraints do not apply to iterative reduplication, whose form is different from the other two aspects, in that the reduplication cycles are separated by pauses. Since there is no formal difference between habituals and continuatives in the data, it is suggested that this semantic distinction may not be grammaticalized in the language, and that, possibly, the inflectional system of NGT instead more broadly distinguishes imperfective/perfective viewpoint. While this latter suggestion is in line with findings reported for many spoken languages, the results are different from what has previously been described for NGT as well as for other sign languages. Potential explanations for these differences can be found in both methodological and sociolinguistic factors.